2016
DOI: 10.1117/1.oe.55.12.124106
|View full text |Cite
|
Sign up to set email alerts
|

Measuring spatially varying, multispectral, ultraviolet bidirectional reflectance distribution function with an imaging spectrometer

Abstract: Abstract. The bidirectional reflectance distribution function (BRDF) data in the ultraviolet (UV) band are valuable for many applications including cultural heritage, material analysis, surface characterization, and trace detection. We present a BRDF measurement instrument working in the near-and middle-UV spectral range. The instrument includes a collimated UV light source, a rotation stage, a UV imaging spectrometer, and a control computer. The data captured by the proposed instrument describe spatial, spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…RCS is wavelength and surface material-dependent factor to determine the shape and type of the target. The majority of the prior research on the radar cross-section and BRDF is reported up to 1060 nm wavelength (Zhang et al 2010;Wang and Ni-Meister 2019;Mungan 2000;Matthew et al 2012;Li et al 2016). Researchers in Hasan et al (2015) used Walthall BDRF model to estimate the RGB color value associated with LiDAR cloud-point by applying point by point BRDF correction approach for homogenous areas and is focused on the improvement of LiDAR cloud-point data.…”
Section: Introductionmentioning
confidence: 99%
“…RCS is wavelength and surface material-dependent factor to determine the shape and type of the target. The majority of the prior research on the radar cross-section and BRDF is reported up to 1060 nm wavelength (Zhang et al 2010;Wang and Ni-Meister 2019;Mungan 2000;Matthew et al 2012;Li et al 2016). Researchers in Hasan et al (2015) used Walthall BDRF model to estimate the RGB color value associated with LiDAR cloud-point by applying point by point BRDF correction approach for homogenous areas and is focused on the improvement of LiDAR cloud-point data.…”
Section: Introductionmentioning
confidence: 99%
“…Since phenols typically expose absorption in the ultra-violet (UV) range (Dearden & Forbes, 1959) with peaks between 260 -300 nm, the UV spectrum poses another spectral range of interest. UV hyperspectral imaging is yet quite unexplored with limited applications (Li, Lyu, Liao, & Wu, 2016;Merkel, 2015) due to increased difficulties in the imaging process. Not only are UV HSI cameras hardly available and still a subject of research (Hsu et al, 2017;Zucco, Caricato, Egidi, & Pisani, 2015), broadband light sources in wavelengths under 400 nm with sufficient illuminance are very scarce.…”
Section: Introductionmentioning
confidence: 99%